Novel geochemical fingerprints of biogenicity applied to ancient carbonates - Gallagher, Meabh (Trinity College (Dublin, Ireland). Department of Geology, 2016)
The oxygenation of the Earth’s surface shaped our planetary environment, fundamentally altered global biogeochemical cycles, and ultimately paved the way for the rise of complex animals at the beginning of the Cambrian. The Earth’s surface oxygenation was apparently achieved in two broad steps at the beginning and the end of the Proterozoic eon. However, reconstruction of the detailed redox-evolution of the Earth’s surface environment remains one of the greatest scientific challenges in the geosciences. Both postulated oxidation events were apparently accompanied by global glaciations, but the causality between the apparent step increases in oxygen concentrations, and these two global glaciation events remains unclear. Marine sedimentary rocks hold great potential for the reconstruction of Precambrian atmospheric and oceanic redox evolution. However, most of the currently available information has been derived from deep-water sedimentary rocks. This thesis presents geochemical investigations - chemical fingerprints – of microbial carbonates spanning from Palaeoarchaean to Cambrian in age. The samples have demonstrably formed in shallow water. Several types of geochemical proxies, including non-vital trace metals, redox sensitive vital metals, and S-isotopes were analysed to study their response to Earth’s oxidation. The work has revealed the following new insights: there is a clear temporal evolution of reduced carbon and pyrite preservation; microbial carbonate-hosted pyrite chemistry mirrors that of black shale-hosted pyrite and confirms changes in fluxes to the ocean with time; S-isotopes in the Neoarchaean ocean record local signals and the S-cycle of that time can be compared to the atmospheric Pb pollution event of the 19th and 20th centuries; and microbial carbonates differ from sponge skeletons in trace element distribution. The emerging picture is that MIF S-isotope anomalies disappeared exactly during the Huronian glaciation reflecting the initial build-up of free oxygen (and ozone) in the atmosphere, resulting in a reorganisation of the greenhouse structure, causing the icehouse. Thus, the initial oxidation of Earth’s surface is not likely an expression of biological evolution, but a response to the global geological functioning of our planet. The Neoproterozoic global glaciations are currently attributed to a tectonic context. However, the findings from this thesis suggest that metazoans could have appeared in the deep Cryogenian, and that they may have contributed to the ventilation of the ocean in the Neoproterozoic oxidation event. Thus the possibility arises that the Neoproterozoic glaciations could have been caused by the rise of metazoans rather than the other way round. The oxygenation of the Earth’s surface shaped our planetary environment, fundamentally altered global biogeochemical cycles, and ultimately paved the way for the rise of complex animals at the beginning of the Cambrian. The Earth’s surface oxygenation was apparently achieved in two broad steps at the beginning and the end of the Proterozoic eon. However, reconstruction of the detailed redox-evolution of the Earth’s surface environment remains one of the greatest scientific challenges in the geosciences. Both postulated oxidation events were apparently accompanied by global glaciations, but the causality between the apparent step increases in oxygen concentrations, and these two global glaciation events remains unclear. Marine sedimentary rocks hold great potential for the reconstruction of Precambrian atmospheric and oceanic redox evolution. However, most of the currently available information has been derived from deep-water sedimentary rocks. This thesis presents geochemical investigations - chemical fingerprints – of microbial carbonates spanning from Palaeoarchaean to Cambrian in age. The samples have demonstrably formed in shallow water. Several types of geochemical proxies, including non-vital trace metals, redox sensitive vital metals, and S-isotopes were analysed to study their response to Earth’s oxidation. The work has revealed the following new insights: there is a clear temporal evolution of reduced carbon and pyrite preservation; microbial carbonate-hosted pyrite chemistry mirrors that of black shale-hosted pyrite and confirms changes in fluxes to the ocean with time; S-isotopes in the Neoarchaean ocean record local signals and the S-cycle of that time can be compared to the atmospheric Pb pollution event of the 19th and 20th centuries; and microbial carbonates differ from sponge skeletons in trace element distribution. The emerging picture is that MIF S-isotope anomalies disappeared exactly during the Huronian glaciation reflecting the initial build-up of free oxygen (and ozone) in the atmosphere, resulting in a reorganisation of the greenhouse structure, causing the icehouse. Thus, the initial oxidation of Earth’s surface is not likely an expression of biological evolution, but a response to the global geological functioning of our planet. The Neoproterozoic global glaciations are currently attributed to a tectonic context. However, the findings from this thesis suggest that metazoans could have appeared in the deep Cryogenian, and that they may have contributed to the ventilation of the ocean in the Neoproterozoic oxidation event. Thus the possibility arises that the Neoproterozoic glaciations could have been caused by the rise of metazoans rather than the other way round.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin